1998
DOI: 10.1590/s0034-71081998000400005
|View full text |Cite
|
Sign up to set email alerts
|

Variação espacial e temporal da produtividade primária pelo fitoplâncton na represa de Jurumirim (Rio Paranapanema, SP)

Abstract: Spatial and temporal variations on the primary productivity by the phytoplankton in Jurumirim Reservoir (Paranapanema River, São Paulo, Brazil)A study on the spatial and temporal variations of the primary productivity by phytoplankton was conducted in Jurumirim Reservoir (Paranapanema River, São Paulo, Brazil) from October, 1995 to July, 1996. Six sampling stations were selected, three in Paranapanema Arm, two in Taquari Arm and one in das Posses Arm. The C 14 method was used for measuring the primary producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
16

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 11 publications
1
17
0
16
Order By: Relevance
“…Canoas I and Canoas II, the newest reservoirs in the Paranapanema cascade, were the ones with lower phytoplankton diversity. The Jurumirim spatial complexity effect on the phytoplankton productivity and structure has been already well demonstrated (Henry et al, 1998;Nogueira, 2000). Another particularity that influences richness and diversity is the connectivity with lateral wetlands, mainly with seasonal or permanent lakes containing a huge amount of different microhabitats (macrophyte-dominated).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Canoas I and Canoas II, the newest reservoirs in the Paranapanema cascade, were the ones with lower phytoplankton diversity. The Jurumirim spatial complexity effect on the phytoplankton productivity and structure has been already well demonstrated (Henry et al, 1998;Nogueira, 2000). Another particularity that influences richness and diversity is the connectivity with lateral wetlands, mainly with seasonal or permanent lakes containing a huge amount of different microhabitats (macrophyte-dominated).…”
Section: Discussionmentioning
confidence: 84%
“…Before the zone of the influence of the first dam (Upstream of Jurumirim), where fluvial conditions and high productivity predominate (Henry et al, 1998;Nogueira, 2000), all the main algae groups were well represented. In the stratified lacustrine environments of Jurumirim and Chavantes Reservoirs, the assemblages were dominated by small unicellular diatoms, mainly D. stelligera.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…trematodes) can be the result of changing overall abiotic factors and, particularly, changes to the intermediate host community that lead to parasite homogenization. Previous studies have identified a significant reduction in potential intermediate host communities (zooplankton and benthic communities), and thereafter a proportional decrease in fish density and diversity in the Jurumirim Reservoir (Henry et al 1998, Mitsuka andHenry 2002). All these are key factors which maintain parasite dynamics.…”
Section: Discussionmentioning
confidence: 95%